Invisible labor, invisible bodies: how the global political economy affects reproductive freedom in the Philippines. Issue 1 (2nd January 2017) - Tanyag, Maria
ABSTRACT: Feminist scholars have critically demonstrated the links between the global political economy, social reproduction and gender-based violence. This article builds on this scholarship by investigating restrictions to reproductive freedom and their connection to the depletion of women's bodies in the global political economy. Specifically, I use the Depletion through Social Reproduction (DSR) framework to reveal how the work of social reproduction is harnessed to service economic activity at the cost of rights to bodily integrity with the aid of religious fundamentalist ideologies that (re)inscribe discourses of female altruism such as the "self-sacrificing mother" ideal. Drawing on the case of the Philippines, I argue that the control of women's bodies is integral to the Philippines' economic strategy of exporting care workers in a competitive global political economy. This strategy is abetted by local Catholic religious fundamentalists who challenge reproductive rights reform at various levels of policy-making and legitimize the lack of investment to sustain social reproduction in the household, community and country as a whole. This article suggests that the neoliberal global economy is increasingly reproduced through women's labor at the cost of their bodily integrity and reproductive freedoms.